2007
DOI: 10.1097/mpg.0b013e31802c41b7
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Rice‐based Oral Rehydration Solution Containing Recombinant Human Lactoferrin and Lysozyme in Peruvian Children With Acute Diarrhea

Abstract: Addition of recombinant human lactoferrin and lysozyme to a rice-based oral rehydration solution had beneficial effects on children with acute diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 30 publications
5
74
1
1
Order By: Relevance
“…A study of 140 Peruvian children with acute watery diarrhea and dehydration showed that adding recombinant human lactoferrin and lysozyme (Ventria Bioscience, Sacramento, CA) to oral rehydration solution reduced the duration of diarrhea (3.7 days vs. 5.2 days, p = 0.05) and relapse after 48 h (9% vs. 19%) [53].…”
Section: Clinical Studies Of Lactoferrin's Effect On Enteric Pathogensmentioning
confidence: 99%
“…A study of 140 Peruvian children with acute watery diarrhea and dehydration showed that adding recombinant human lactoferrin and lysozyme (Ventria Bioscience, Sacramento, CA) to oral rehydration solution reduced the duration of diarrhea (3.7 days vs. 5.2 days, p = 0.05) and relapse after 48 h (9% vs. 19%) [53].…”
Section: Clinical Studies Of Lactoferrin's Effect On Enteric Pathogensmentioning
confidence: 99%
“…Safety relevant endpoints were not studied. In two studies in Peruvian children which reported on adverse events the number of adverse events did not differ between the treatment and the placebo group and no adverse event could be attributed to the test substance (Ochoa et al, 2008;Zavaleta et al, 2007).…”
Section: Studies In Childrenmentioning
confidence: 99%
“…Four published studies with a duration of fifteen days to nine months investigated presumed antimicrobial effects of bLF at intakes between 100 and 1,000 mg per day alone or in coadministration with other substances (Ajello et al, 2002;Egashira et al, 2007;Ochoa et al, 2008;Zavaleta et al, 2007). Safety relevant endpoints were not studied.…”
Section: Studies In Childrenmentioning
confidence: 99%
“…In a research to investigate the efficacy of R-ORS compared to G-ORS, in treating children with acute watery diarrhea, R-ORS was more effective in reducing the duration of diarrhea and hospital stay, although no significant effect was found on stool output or intravenous fluid administering frequency (15). Some other studies have found no significant difference between R-ORS and G-ORS in the treatment of children with diarrhea (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%